Optimization model for a flood evacuation assignment problem: a case study - Ahmad Yusoff, Siti Syafiqah; Benjamin, Aida Mauziah; Abd Rahman, Rosshairy; Abdul-Rahman, Syariza (AIP Publishing LLC, 2019)
Evacuation is a vital step in emergency management, in which people are transported from danger to safety to reduce or avoid casualties i.e. injuries or death. During evacuation, shelters become crowded to victims and this could be chaotic. The present assignment of victims to shelters is performed manually by the rescue team and this requires much time and massive manpower to ensure good distribution. Hence, a viable system is sought in assigning victims to shelters so as to provide better victims distribution. In this paper, a mathematical model, particularly binary integer programming (BIP) model, was formulated to solve a real case study of flood evacuation assignment issue that took place in southern Malaysia. The BIP model can be applied to assign flood victims to the available shelters subject to problem constraints with the objective of minimizing the total distance. The real data used in this study involved 33 families of flood victims selected from six available shelters. The optimal solution obtained from the BIP model showed that two families were assigned to Shelter 1, while shelters 2 until 4 were assigned with seven families each, six families to Shelter 5, and the remaining four families were assigned to Shelter 6 with the total distance of 13.61 km. The optimal solution is similar with the solution implemented by the rescue team that was devised manually. However, by using the BIP model, the solution retrieved from the model can easily be obtained and saves much of the precious time amongst the rescue teams.